DESIGN OF ILLUSTRATION BOOK ON WASTE MANAGEMENT EDUCATION FOR CHILDREN - Julana, Farah Fahira; Siswanto, Riky Azharyandi; Utami, Lira Anindita (Telkom University, 2024)
Improper waste management results in environmental contamination, affecting land,water, and air quality. This contamination fosters disease-spreading animals like rats,cockroaches, and mosquitoes. Indonesia ranks as the world9s second-largest plastic wastecontributor, generating 14.96 million tons annually with 6.8 million tons unprocessed due to lowawareness and weak regulations. The habit of littering of adults can be passed onto theirchildren, highlighting the importance of teaching waste management to young children forenvironmental care and discipline. This research aims to raise awareness using qualitative andquantitative data to produce an educational illustration book to instil waste managementprinciples in children and shape their character. Keywords: Children, Education, Illustration Book, Waste Management